Synthesis, Characterization, Antimicrobial Activity and Antioxidant of Azo Schiff Bases Containing Sulfanilamide - Bushra K. AL-Salami (Journal of Global Pharma Technology, 2018)
Some new azo Schiff bases (SH1-SH6, SH14) were prepared in good yields by reaction of Sulfanilamide with 2, 4-dihydroxy-5-(phenyldiazyl) benzaldehyde and its substituted derivatives (Z1-Z6, Z14). The structures of azo and azo-azomethine compounds were determined by FT-IR, 1HNMR spectroscopic techniques, EI-mass and elemental analysis. The azo-azomethine compounds have been tested in vitro against Pseudomonas aeruginosa (-Ve) gram and Staphylococcus sciuri (+ Ve) gram in order to assess their antibacterial characteristic. Antioxidant efficiency of the azo-azomethine compounds examined.Keywords: Azo-azomethine, Azo compound, antioxidantand antibacterial activity, Sulfanilamide.